EFFORTS TO IMPROVE THE COMPETENCY OF PROFESSIONALISM TEACHER IN JEMBER REGENCY: Fahrudi Ahwan Ikhsan, Fahmi Arif Kurnianto, Bejo Apriyanto , Elan Artono Nurdin - Fahrudi Ahwan Ikhsan; Fahmi Arif Kurnianto; Bejo Apriyanto; Elan Artono Nurdin (Department of Geography Education, University of Jember, 2017)
This study aims to explain the condition of professionalism and efforts to improve the competence of teachers IPS in Jember District. The sampling technique was done by random sampling which amounted to 55 person. Methods of data collection with questionnaires and documentation. Data analysis uses a percentage descriptive. The result of the research shows that the competency of professionalism of IPS teachers is as follows: the acquisition of materials, concepts and scholarship of IPS teachers is 87.25% in the high category, the development of learning materials supported by IPS teachers creatively is 92.04% including in the high category; mastery of basic competence and basic competence by 87.05% including high category, utilization of communication technology for self-development of IPS teachers of 86.35% included in the high category. In general, the competency of professionalism of IPS teachers in Jember district is categorized as high, namely 88.17%, while the effort to increase the professional competence of IPS teachers as follows: joining the training and seminar of 66.81% low category; developing syllabus and IPS RPP of 70.50%; doing PTK 48.95% low category; develop science of technology in learning 74.82% high category. Overall, the effort to improve the professionalism competence of IPS Junior High School teachers in Jember District is 71.34 included in the high category. Key words: Professionalism Competence, IPS Teachers References Agung, Iskandar . 2012. Panduan Penelitian Tindakan Kelas bagi Guru. Jakarta: Bestari Musfah, Jejen. 2011. Peningkatan Kompetensi Guru. Jakarta. Kencana Prenada. Sanjaya, Wina. 2006. “Strategi Pembelajaran Berorientasi Standar Proses. Jakarta : Kencana Prenada Media Sumiati. 2007. Metode Pembelajaran Pendekatan Individual. Bandung: Rancaekek Kencana. Copyright (c) 2017 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License